Edible Flowers: Study Involving Consumers In Portugal, Slovenia And Brazil - Guiné, Raquel (2019)
Introduction: The use of edible flowers (EF) has gained a renewed attention because of their potential for gastronomic purposes allied to their possible beneficial health effects. However, there is still a lack of information about consumer’s behaviours regarding EF and how much they are informed about these products. Objectives: The aim of this study was to investigate the habits and knowledge about EF for people residing in three different countries, located in different parts of the world (Portugal in the Iberian Peninsula, Slovenia in South Central Europe and Brazil in South America). Methods: This is a cross-sectional study carried out with a sample of 559 participants from the three countries mentioned above. For data analysis, basic descriptive statistical tools were used complemented with a tree classification analysis, aimed at evaluating the relative importance of each of the possible influential variables (age group, sex, country, living environment, level of education and area of work/studies) on the participants’ consumption and knowledge about EF. For that purpose, it was followed the CRT (Classification and Regression Trees) algorithm with cross validation. Results: In general, the participants had already consumed EF and their use was more popular between the Portuguese participants, being the Brazilian those who used them less. Also, most of the participants, independently of the country, showed some uncertainty regarding the increase in the consumption of EF, which reveals that there are still some doubts about the use of EF in gastronomy. The classification analysis showed that country was the major discriminant for aspects like: the consumption of EF, their usage in gastronomy, the preferred way to eat EF and also for the level of awareness associated with the consumption of this kind of product. On the other hand, level of education was the most important discriminant for the information available about EF and also for the participants' opinions towards increasing the intake of EF. Conclusions: These results highlighted the importance of the country and other sociodemographic characteristics on EF eating patterns. These findings are very useful to understand the factors that most affect the participants’ attitudes towards the consumption and knowledge regarding EF.